2009
DOI: 10.1007/s00296-009-0980-x
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of performance of anti-cyclic citrullinated peptide 2 and citrullinated protein antibodies in the diagnosis of rheumatoid arthritis in Iranian patients

Abstract: Antibodies to citrullinated proteins and rheumatoid factor (RF) are widely used in patients with rheumatoid arthritis (RA) and the antibodies to citrullinated proteins appear to be the most specific markers of the disease. The objective was to compare the diagnostic performance of the anti-cyclic citrullinated peptide 2 (anti-CCP2) and citrullinated protein Antibodies (CPA) with RF in the diagnosis of RA. Serum samples of 139 patients with RA and 131 patients with other rheumatic diseases were checked for anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 30 publications
2
7
0
Order By: Relevance
“…In our study the sensitivity and specificity of RF were 46.2 and 90.29%, respectively. These values are similar to those reported by Aflaki using latex fixation test [9] but are different from Hodkinson's study [15]. A literature review shows that the sensitivity of RF in RA has ranged from 26 to 90 percent [16].…”
Section: Rfsupporting
confidence: 69%
See 1 more Smart Citation
“…In our study the sensitivity and specificity of RF were 46.2 and 90.29%, respectively. These values are similar to those reported by Aflaki using latex fixation test [9] but are different from Hodkinson's study [15]. A literature review shows that the sensitivity of RF in RA has ranged from 26 to 90 percent [16].…”
Section: Rfsupporting
confidence: 69%
“…For example, Moghimi et al [8] showed that the overall performance of the anti-CCP and RF tests for differentiating RA and other inflammatory polyarthritis were similar [8]. Meanwhile in another research Aflaky et al [9] revealed that AUC (Area under the Curve) for anti-CCP was higher than that for RF and concluded that anti-CCP might be of a better diagnostic value than RF test [9]. On the other hand, Abolghasemi et al [10] offers a combination of these tests rather than anti-CCP or RF to get the best results in RA diagnosis and prognosis [10].…”
Section: Introductionmentioning
confidence: 99%
“…Most studies on the diagnostic utility of the aCCP test in RA have been done in industrialized countries on subjects of European ancestry [6], with only a few done in the developing world [7][8][9][10]. In the absence of any published studies on the prevalence and specificity of aCCP in RA in sub-Saharan Africa, we undertook a cross-sectional case-control study to establish the diagnostic utility of the RF and aCCP tests in urbanized Black South Africans with early RA.…”
mentioning
confidence: 99%
“…In another study conducted by Saraux et al (2003) sensitivity of RF Latex test was 45%. In a different study Aflaky et al (2010) reported similar values of RF Latex test. Nishimura et al (2007) reported that sensitivity of RF is 69% and specificity is 85%.…”
Section: Discussionmentioning
confidence: 52%